Association of glutathione S-transferase GSTM1 and GSTT1 deletion polymorphisms with obesity and their relationship with body mass index, lipoprotein and hypertension among young age Saudis. (September 2016) - Almoshabek, Hamoud A; Mustafa, Md; Al-Asmari, Mohammed M; Alajmi, Tahani K; Al-Asmari, Abdulrahman K
Objectives: Persistent oxidative stress is one of the several risk factors that may be associated with the etiology of obesity. The present study is aimed to investigate association between GSTM1 and GSTT1 polymorphisms with obesity and their relationship with plasma lipoproteins, body mass index (BMI) and hypertension. Design: The GSTM1 and GSTT1 deletion polymorphisms were analyzed by multiplex polymerase chain reaction. The lipoproteins were measured in plasma using commercially available kit and the weight, height, systolic (SBP) and diastolic (DBP) blood pressures by standard procedure of measurements. Setting: Prince Sultan Military Medical City, Riyadh Saudi Arabia. Participants: A total of 420 overweight/obese cases and 234 normal weight controls belong to young age Saudis. Main outcomes measures: GSTM1 / GSTT1 polymorphisms may be associated with obesity. Results: Weight, BMI, low-density lipoprotein (LDL) and SBP were significantly higher while high-density lipoprotein (HDL) was significantly lower in cases in comparison to controls. Frequency of GSTM1 +/ GSTT1 − (OR = 2.70, 95% CI = 1.52–4.81, p  = <0.001) and GSTM1 −/ GSTT1 − (OR = 2.43, 95% CI = 1.15–5.15, p  = 0.018) was significantly higher in cases as compared to controls. BMI and weight were significantly higher in GSTM1 +/ GSTT1 − and GSTM1 −/ GSTT1 − genotypes, and LDL, DBP and SBP significantly higher in GSTM1 −/ GSTT1 − null genotype while HDL was significantly lower in GSTM1 −/ GSTT1 + and GSTM1 −/ GSTT1 − genotypes in comparison to GSTM1 +/ GSTT1 + genotype. Conclusions: The GSTM1 +/ GSTT1 − and GSTM1 −/ GSTT1 − null genotypes were significantly associated with obesity and have shown relationship with obesity risk factors in cases. Hence, these genes may be associative genetic risk factor for obesity among young age Saudis.